Citizen Science and Research Libraries : Strategie- und kooperative Projektarbeit, Investitionen in offene Kulturdaten und in Anwenderwissen - Munke, Martin; Bemme, Jens (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2019)
How can academic libraries strategically establish and implement Citizen Science as a field of activity, particularly in connection with the functions of a state library? The article discusses this question, using the Saxon State and University Library (SLUB) Dresden as an example. The focus lies on collaborative tools and approaches for research projects and library work with open cultural data from GLAM institutions. Specifically covered are data relevant to regional studies and how this data can be linked and used in Citizen Science projects. As is shown, libraries should not only use digitisation programmes to provide data and services, but should also offer additional methodological knowhow for Citizen Science research. The authors argue that the combination of Openness and Citizen Science as Open Citizen Science is an exemplary approach for the positioning of state and academic libraries within the regional scientific and cultural sector - especially in their role as providers of a public digital infrastructure.